Environment-friendly high-hardness flexible liquid ceramic
By combining epoxy oligosiloxane resin and polysiloxane copolymer in liquid ceramics, and adding ceramic microspheres, nanosilica and potassium aluminosilicate, and using end-aminopolyurea and amine-based curing agents Component B solves the problem of high hardness but high brittleness in traditional ceramic coating materials, and realizes liquid ceramic materials that have both high hardness and flexibility. It has excellent high temperature resistance, chemical corrosion resistance and acid-base environmental stability. It is also suitable for low-temperature curing to meet the needs of environmental protection and easy construction.
Patent Information
- Application Number
- CN202411501679.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Traditional ceramic coating materials have problems such as high hardness but high brittleness and insufficient toughness, which limits their widespread promotion in occasions where impact resistance and flexibility are required.
By combining epoxy oligosiloxane resin and polysiloxane copolymer in liquid ceramics, and adding ceramic microspheres, nanosilica and potassium aluminosilicate, and using end-aminopolyurea and amine-based curing agents Component B achieves both high hardness and flexibility.
It achieves high hardness and flexibility of liquid ceramics, with excellent high temperature resistance, chemical corrosion resistance and acid-base environmental stability, and is also suitable for low-temperature curing to meet environmental protection and easy construction needs.
Smart Images

Figure BDA0005102765860000071 
Figure BDA0005102765860000081 
Figure BDA0005102765860000082
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an environmentally friendly liquid ceramic with high hardness and flexibility. Background Art
[0002] Liquid ceramics, as a new type of material with both inorganic and organic components, have been widely used in modern industrial fields, especially in coatings, protective layers and high-performance films. Liquid ceramic materials are widely used in aerospace, automobile manufacturing, electronic equipment, and architectural decoration due to their excellent wear resistance, high temperature resistance, and corrosion resistance. However, traditional ceramic coating materials often have the problem of high hardness but high brittleness and insufficient toughness, which limits their widespread promotion in practical applications, especially in situations where both impact resistance and flexibility are required.
[0003] In order to overcome these problems, there has been a research trend in recent years to modify inorganic ceramic materials through organic modification. These materials aim to improve the toughness and flexibility of the coating by introducing organic polymers into the ceramic coating, so that the material has both high hardness and toughness. In particular, the emergence of silicone ceramic coatings has further improved the performance of traditional ceramic coatings. Silicone resin has become an ideal coating substrate due to its excellent weather resistance, chemical corrosion resistance and thermal stability. At present, coatings based on composite material systems such as alkoxysilane, silica sol and acrylic emulsion have shown excellent mechanical properties and environmental friendliness. However, how to further improve the flexibility and comprehensive performance of the coating through the synergistic effect of silicone and polymers remains a technical problem. In addition, the demand for room temperature curing coatings is increasing to meet application scenarios that do not require high temperature baking. Therefore, the development of an environmentally friendly, easy-to-apply liquid ceramic coating with high hardness and flexibility has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] Based on the problems existing in the background technology, the present invention provides an environmentally friendly liquid ceramic with high hardness and flexibility.
[0005] The present invention is implemented by the following technical solutions:
[0006] An environmentally friendly liquid ceramic with high hardness and flexibility, comprising component A and component B, wherein component A comprises the following components by weight: 30-40 parts of epoxy oligosiloxane resin, 10-20 parts of polysiloxane copolymer, 4-8 parts of potassium aluminosilicate, 5-10 parts of ceramic microspheres, 2-5 parts of nano-silicon dioxide, and 1-3 parts of additives;
[0007] Component B comprises the following components by weight: 20-30 parts of amino-terminated polyurea and 5-10 parts of amine curing agent.
[0008] Furthermore, the preparation method of the epoxy oligomeric siloxane resin is specifically as follows: phenyl triethoxysilane, tetraethyl silicate and γ-glycidyloxypropyl trimethoxysilane are added to a mixed solution of ethanol and deionized water, stirred at 60°C for 30 minutes, then hydrochloric acid is added, heated at 60°C for condensation and reflux for 12 hours, and after the reaction is completed, low-boiling substances are removed by reduced pressure distillation to obtain the epoxy oligomeric siloxane resin.
[0009] Furthermore, the molar ratio of phenyltriethoxysilane, tetraethyl silicate and γ-glycidyloxypropyltrimethoxysilane is (1.2-1.6):(0.4-0.8):1.
[0010] Further, the weight ratio of ethanol to deionized water is (30-40):10;
[0011] The weight of ethanol is 2-3 times the weight of γ-glycidyloxypropyltrimethoxysilane;
[0012] The weight of hydrochloric acid is 10-20% of the weight of γ-glycidyloxypropyltrimethoxysilane.
[0013] Furthermore, the preparation method of the polysiloxane copolymer is specifically as follows: phenyltriethoxysilane is added to a reaction kettle, and a hydrochloric acid aqueous solution with a mass concentration of 0.1-2% is added dropwise at 5-10° C. After the addition is completed, the temperature is raised to 65° C., and the reaction is carried out for 2-3 hours. A hydroxyl-terminated polysiloxane is continuously added, and the temperature is raised to 110° C., and the reaction is carried out for 2-3 hours. After the reaction is completed, low-boiling substances are removed by reduced pressure distillation to obtain a polysiloxane copolymer.
[0014] Furthermore, the mass ratio of phenyltriethoxysilane, hydrochloric acid aqueous solution and hydroxyl-terminated polysiloxane is (2-10):(0.3-1.6):1.
[0015] Furthermore, the additives include a leveling agent, a defoaming agent and a dispersant in a mass ratio of (1-2): (1-2): (1-2);
[0016] The leveling agent is polyether modified polymethyl alkyl siloxane, the defoaming agent is polysiloxane defoaming agent, and the dispersant is BYK-2055.
[0017] Furthermore, the amino-terminated polyurea is prepared by reacting polyetheramine D400 and isophorone diisocyanate.
[0018] Furthermore, it also includes a solvent, and the solvent is propylene glycol methyl ether acetate.
[0019] The present invention also discloses a method for preparing an environmentally friendly liquid ceramic with high hardness and flexibility, comprising the following steps:
[0020] (1) Prepare corresponding weight portions of raw materials according to the formula;
[0021] (2) adding epoxy oligosiloxane resin, polysiloxane copolymer, ceramic microspheres, defoamer and dispersant into a container, dispersing at high speed for 20 minutes, grinding and dispersing with a grinder to a fineness of 1-10 microns, adding potassium aluminosilicate, nano-silica and leveling agent, dispersing at high speed for 30 minutes, and finally adding solvent to adjust viscosity and solid content to obtain component A;
[0022] (3) Mix the amino-terminated polyurea and the amine curing agent to obtain component B.
[0023] Beneficial effects of the present invention:
[0024] 1. The combination of epoxy oligosiloxane resin and polysiloxane copolymer in component A of the present invention can provide high hardness of liquid ceramics while maintaining a certain degree of flexibility. The cross-linking reaction between epoxy groups and siloxane can provide higher structural strength, while the flexible segments (polysiloxane) in the polysiloxane copolymer can give the material excellent flexibility. At the same time, epoxy oligosiloxane resins and polysiloxane copolymers have excellent high temperature resistance and chemical corrosion resistance, especially the stability of the silicon oxygen bond enables the material to maintain its performance at high temperatures and in harsh chemical environments. Both the epoxy groups and silicon oxygen bonds in the material have good resistance to acid-base environments, ensuring that the material can remain stable in acid-base environments. Ceramic microspheres, nano-silica and potassium aluminosilicate as fillers can further improve the hardness of the material, especially in the microstructure by forming a dense particle reinforcement network, further improving the surface hardness (exceeding 9H) without significantly reducing flexibility.
[0025] 2. The combination of the mid-terminal amino polyurea and the amine curing agent in the present invention allows component B to be quickly cured with component A under low temperature conditions. Polyurea curing agents have high reactivity and can quickly cross-link and form a strong network structure at a lower temperature. Therefore, the liquid ceramic in this formula can also be cured in a low temperature environment, which is suitable for different usage scenarios, especially under low temperature construction conditions. Propylene glycol methyl ether acetate, as a solvent, has low volatility and can maintain good solubility and fluidity in a low temperature environment, helping the material to cure smoothly at low temperatures.
[0026] 3. Propylene glycol methyl ether acetate is a low-volatility, low-toxic environmentally friendly solvent that complies with modern environmental regulations on volatile organic compounds (VOC). It can help reduce VOC emissions of materials and meet environmental protection requirements, especially in areas with strict environmental standards (such as architectural coatings, automotive coatings, etc.). The formula does not use traditional highly toxic and polluting solvents or additives. The entire material system is relatively environmentally friendly, which helps reduce the negative impact on the environment and also reduces the health hazards to construction workers. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.
[0028] Example 1
[0029] Preparation method of epoxy oligosiloxane resin
[0030] Phenyltriethoxysilane, tetraethyl silicate and γ-glycidyloxypropyltrimethoxysilane are added to a mixed solution of ethanol and deionized water in a molar ratio of 1.4:0.6:1, the weight ratio of ethanol to deionized water is 30:10, the weight of ethanol is 2.5 times the weight of γ-glycidyloxypropyltrimethoxysilane, stirred at 60°C for 30 minutes, then hydrochloric acid is added, the weight of hydrochloric acid is 15% of the weight of γ-glycidyloxypropyltrimethoxysilane, heated at 60°C for 12 hours, condensed and refluxed, and after the reaction is completed, low boiling points are removed by reduced pressure distillation to obtain epoxy oligomeric siloxane resin.
[0031] The preparation method of the polysiloxane copolymer is specifically as follows: phenyltriethoxysilane is added to a reaction kettle, and a hydrochloric acid aqueous solution with a mass concentration of 1% is added dropwise at 5°C. After the addition is completed, the temperature is raised to 65°C, and the reaction is carried out for 2 hours. The hydroxyl-terminated polysiloxane is continuously added, and the temperature is raised to 110°C, and the reaction is carried out for 2 hours. After the reaction is completed, the low-boiling substances are removed by reduced pressure distillation to obtain the polysiloxane copolymer. During the entire reaction process, the mass ratio of phenyltriethoxysilane, hydrochloric acid aqueous solution and hydroxyl-terminated polysiloxane is 6:1:1.
[0032] An environmentally friendly liquid ceramic with high hardness and flexibility, comprising component A and component B, wherein component A comprises the following components by weight: 35 parts of epoxy oligosiloxane resin, 15 parts of polysiloxane copolymer, 6 parts of potassium aluminosilicate, 8 parts of ceramic microspheres, 3 parts of nano-silicon dioxide, 1 part of leveling agent polyether-modified polymethyl alkyl siloxane, 1 part of polysiloxane defoamer and 1 part of dispersant BYK-2055;
[0033] Component B includes the following components by weight: 25 parts of amino-terminated polyurea and 8 parts of amine curing agent.
[0034] A method for preparing an environmentally friendly liquid ceramic having high hardness and flexibility comprises the following steps:
[0035] (1) Prepare corresponding weight portions of raw materials according to the formula;
[0036] (2) adding epoxy oligosiloxane resin, polysiloxane copolymer, ceramic microspheres, defoamer and dispersant into a container, dispersing at high speed for 20 minutes, grinding and dispersing with a sand grinder to a fineness of 1-10 microns, adding potassium aluminosilicate, nano-silica and leveling agent, dispersing at high speed for 30 minutes, and finally adding solvent propylene glycol methyl ether acetate to adjust the viscosity and solid content to obtain component A;
[0037] (3) Mix the amino-terminated polyurea and the amine curing agent to obtain component B.
[0038] In this embodiment, the process of using a sand grinder to grind and disperse to a fineness of 1-10 microns also includes:
[0039] Obtain the grinding power of the sander for grinding to 1-10 microns respectively, and determine the grinding frequency of the sander for grinding to 1-10 microns respectively according to the respective grinding power;
[0040] Determine the oscillation properties of the sanders for grinding to 1-10 microns according to the grinding frequency, wherein the oscillation properties include: basic oscillation and basic oscillation plus load oscillation;
[0041] Determine monitoring torque parameters for grinding to 1-10 microns respectively for the sander according to the oscillation properties, and determine grinding rates for grinding to 1-10 microns respectively for the sander according to the monitoring torque parameters;
[0042] Determine the state monitoring frame interval based on the grinding rate of the sander grinding to 1-10 microns and the grinding morphology of the sander grinding to 1-10 microns;
[0043] The monitoring index and index threshold are set in each frame of the grinding image according to the state monitoring frame distance, and the process state time series characteristics of the grinding machine grinding to 1-10 microns are constructed based on the monitoring index and index threshold;
[0044] Determine the rotation speed timing characteristics of the sander for grinding to 1-10 microns respectively according to the timing characteristics of the process state and the grinding frequencies of the sander for grinding to 1-10 microns respectively;
[0045] Use the Bayesian model to establish the correlation features between the process state timing features and the speed timing features, and determine the speed adjustment parameters of the sander for grinding to 1-10 microns respectively according to the correlation features;
[0046] The grinding speed of the sander is adaptively adjusted by adjusting the speed parameters when grinding to 1-10 microns respectively, and the status is monitored at the same time, and an abnormal reminder is issued when the monitoring status is abnormal.
[0047] The beneficial effects of the above technical solution are: by determining the speed adjustment parameters of the sander for grinding to 1-10 microns respectively, the optimal grinding quality of the grinder can be achieved on the basis of ensuring the grinding effect, thereby improving the grinding reliability and stability. Furthermore, by determining the monitoring indicators and then conducting status monitoring, it can be ensured that the ground product meets actual needs, thereby reducing costs and improving practicality and reliability.
[0048] Example 2
[0049] The difference between this embodiment and embodiment 1 is that component A includes the following components by weight: 35 parts of epoxy oligosiloxane resin, 10 parts of polysiloxane copolymer, 6 parts of potassium aluminosilicate, 8 parts of ceramic microspheres, 3 parts of nano-silica, 1 part of leveling agent polyether modified polymethyl alkyl siloxane, 1 part of polysiloxane defoamer and 1 part of dispersant BYK-2055.
[0050] The rest is the same as in Example 1.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that component A includes the following components by weight: 35 parts of epoxy oligosiloxane resin, 20 parts of polysiloxane copolymer, 6 parts of potassium aluminosilicate, 8 parts of ceramic microspheres, 3 parts of nano-silica, 1 part of leveling agent polyether modified polymethyl alkyl siloxane, 1 part of polysiloxane defoamer and 1 part of dispersant BYK-2055.
[0053] The rest is the same as in Example 1.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that component A includes the following components by weight: 35 parts of polysiloxane resin (phenyltriethoxysilane), 15 parts of polysiloxane copolymer, 6 parts of potassium aluminosilicate, 8 parts of ceramic microspheres, 3 parts of nano-silica, 1 part of leveling agent polyether modified polymethyl alkyl siloxane, 1 part of polysiloxane defoamer and 1 part of dispersant BYK-2055.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 is that component A includes the following components by weight: 35 parts of epoxy oligosiloxane resin, 6 parts of potassium aluminosilicate, 8 parts of ceramic microspheres, 3 parts of nano-silica, 1 part of leveling agent polyether modified polymethyl alkyl siloxane, 1 part of polysiloxane defoamer and 1 part of dispersant BYK-2055.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 1 is that component A includes the following components by weight: 35 parts of epoxy oligosiloxane resin, 30 parts of polysiloxane copolymer, 6 parts of potassium aluminosilicate, 8 parts of ceramic microspheres, 3 parts of nano-silica, 1 part of leveling agent polyether modified polymethyl alkyl siloxane, 1 part of polysiloxane defoamer and 1 part of dispersant BYK-2055.
[0060] Comparative Example 4
[0061] The difference between this comparative example and Example 1 is that the preparation method of the polysiloxane copolymer is specifically as follows: phenyltriethoxysilane is added to a reaction kettle, and a hydrochloric acid aqueous solution with a mass concentration of 1% is added dropwise at 5°C. After the addition is completed, the temperature is raised to 65°C, and the reaction is carried out for 2 hours. The hydroxyl-terminated polysiloxane is continuously added, and the temperature is raised to 110°C, and the reaction is carried out for 2 hours. After the reaction is completed, the low-boiling substances are removed by reduced pressure distillation to obtain the polysiloxane copolymer. During the entire reaction process, the mass ratio of phenyltriethoxysilane, hydrochloric acid aqueous solution and hydroxyl-terminated polysiloxane is 15:1.5:1.
[0062] Comparative Example 5
[0063] The difference between this comparative example and Example 1 is that component B comprises the following components in parts by weight: 33 parts of amino-terminated polyurea.
[0064] Performance Testing
[0065] Pour the A and B components of Examples 1-2 and Comparative Examples 1-6 into a container at a mass ratio of 1:1, use a stirrer to stir at a constant speed of 300 r / min for 2-3 minutes, spray or brush them directly on the sample, and prepare and test them according to the standards. The test standards and test results are shown in Tables 1 and 2 below.
[0066] Table 1
[0067]
[0068]
[0069] Table 2
[0070]
[0071] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An environmentally friendly liquid ceramic with high hardness and flexibility, comprising component A and component B, characterized in that: Component A includes the following components by weight: 30-40 parts of epoxy oligosiloxane resin, 10-20 parts of polysiloxane copolymer, 4-8 parts of potassium aluminosilicate, 5-10 parts of ceramic microspheres, 2-5 parts of nano-silicon dioxide, and 1-3 parts of additives; Component B comprises the following components by weight: 20-30 parts of amino-terminated polyurea and 5-10 parts of amine curing agent.
2. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 1, characterized in that: The preparation method of the epoxy oligomeric siloxane resin is specifically as follows: phenyl triethoxysilane, tetraethyl silicate and γ-glycidyloxypropyl trimethoxysilane are added to a mixed solution of ethanol and deionized water, stirred at 60° C. for 30 minutes, then hydrochloric acid is added, heated at 60° C. for condensation and reflux for 12 hours, and after the reaction is completed, low-boiling substances are removed by reduced pressure distillation to obtain the epoxy oligomeric siloxane resin.
3. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 2, characterized in that: The molar ratio of phenyltriethoxysilane, tetraethyl silicate and γ-glycidyloxypropyltrimethoxysilane is (1.2-1.6):(0.4-0.8):
1.
4. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 2, characterized in that: The weight ratio of ethanol to deionized water is (30-40):10; The weight of ethanol is 2-3 times the weight of γ-glycidyloxypropyltrimethoxysilane; The weight of hydrochloric acid is 10-20% of the weight of γ-glycidyloxypropyltrimethoxysilane.
5. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 1, characterized in that: The preparation method of the polysiloxane copolymer is specifically as follows: phenyltriethoxysilane is added into a reaction kettle, and a hydrochloric acid aqueous solution with a mass concentration of 0.1-2% is added dropwise at 5-10°C. After the addition is completed, the temperature is raised to 65°C, and the reaction is carried out for 2-3 hours. A hydroxyl-terminated polysiloxane is continuously added, and the temperature is raised to 110°C, and the reaction is carried out for 2-3 hours. After the reaction is completed, low-boiling substances are removed by reduced pressure distillation to obtain a polysiloxane copolymer.
6. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 5, characterized in that: The mass ratio of phenyltriethoxysilane, hydrochloric acid aqueous solution and hydroxyl-terminated polysiloxane is (2-10):(0.3-1.6):
1.
7. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 1, characterized in that: The additives include a leveling agent, a defoamer and a dispersant in a mass ratio of (1-2): (1-2): (1-2); The leveling agent is polyether modified polymethyl alkyl siloxane, the defoaming agent is polysiloxane defoaming agent, and the dispersant is BYK-2055.
8. The environmentally friendly liquid ceramic with high hardness and flexibility according to claim 1, characterized in that: The amino-terminated polyurea is prepared by the reaction of polyetheramine D400 and isophorone diisocyanate.
9. The environmentally friendly, high-hardness and flexible liquid ceramic according to claim 1, characterized in that: It also includes a solvent, and the solvent is propylene glycol methyl ether acetate.
10. A method for preparing an environmentally friendly liquid ceramic with high hardness and flexibility as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Prepare corresponding weight portions of raw materials according to the formula; (2) adding epoxy oligosiloxane resin, polysiloxane copolymer, ceramic microspheres, defoamer and dispersant into a container, dispersing at high speed for 20 minutes, grinding and dispersing with a grinder to a fineness of 1-10 microns, adding potassium aluminosilicate, nano-silica and leveling agent, dispersing at high speed for 30 minutes, and finally adding solvent to adjust viscosity and solid content to obtain component A; (3) Mix the amino-terminated polyurea and the amine curing agent to obtain component B.
Citation Information
Patent Citations
Polyphenyl methylsiloxane modified epoxy resin and manufacturing method of high performance electronic packaging material thereof
CN101665571A
Dendritic polyurea for solubilizing active substances of low solubility
CN102612318A
Anticorrosive coating used on inner wall of desulfurization and denitrification device and preparation method thereof
CN105086772A
Epoxy polysiloxane paint and preparing method
CN105838192A
Epoxy silicone resin seal material of light emitting apparatus and preparation method thereof
CN105977368A